Effects of phosphorylation by protein kinase A on binding of catecholamines to the human tyrosine hydroxylase isoforms - Sura, Giri R. (2004)
Tyrosine hydroxylase (TyrH), the catalyst for the key regulatory step in catecholamine biosynthesis, is phosphorylated by cAMP-dependent protein kinase A (PKA) on a serine residue in a regulatory domain. In the case of the rat enzyme, phosphorylation of Ser40 by PKA is critical in regulating the enzyme activity; the effect of phosphorylation is to relieve the enzyme from inhibition by dopamine and dihydroxyphenylalanine (DOPA). There are four isoforms of human tyrosine hydroxylase (hTyrH), differing in the size of an insertion after Met30. The effects of phosphorylation by PKA on the binding of DOPA and dopamine have now been determined for all four human isoforms. There is an increase of about two-fold in the K(d) value for DOPA for isoform 1 upon phosphorylation, from 4.4 to 7.4 μM; this effect decreases with the larger isoforms such that there is no effect of phosphorylation on the K(d) value for isoform 4. Dopamine binds more much tightly, with K(d) values less than 3 nM for all four unphosphorylated isoforms. Phosphorylation decreases the affinity for dopamine at least two orders of magnitude, resulting in K(d) values of about 0.1 μM for the phosphorylated human enzymes, due primarily to increases in the rate constant for dissociation of dopamine. Dopamine binds about two-fold less tightly to the phosphorylated isoform 1 than to the other three isoforms. The results extend the regulatory model developed for the rat enzyme, in which the activity is regulated by the opposing effects of catecholamine binding and phosphorylation by PKA. The small effects on the relatively high K(d) values for DOPA suggest that DOPA levels do not regulate the activity of hTyrH.